Perubahan Penggunaan Lahan dan Dampaknya Terhadap Koefisien dan Volume Limpasan Banjir Di Das Keureuto, Provinsi Aceh (Land-Use Changes and Their Impact on Runoff Coefficient and Flood Volume in the Keureuto Watershed, Aceh Province) - Cut Azizah; Cut Nofita; Halus Satriawan; Ridwan Iriadi; Sarif Robo; Misnawati (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2025)
Land-use changes significantly impact watershed hydrology, including increased surface runoff and flood risk. This study uses the Soil Conservation Service–Curve Number (SCS-CN) method to evaluate the impact of land-use changes on the runoff coefficient (C) and flood runoff volume in the Keureuto Watershed in Aceh Province. . Land-use data were analyzed from four time periods: 1990, 2000, 2010, and 2024. Rainfall, soil type, and elevation data were used to calculate CN values, runoff volume, and the runoff coefficient. A land-use transition matrix was used to identify land use conversion patterns, and integrated them into a geographic information system (GIS) for spatial analyses. The results show significant increases in the area of settlements (82.9%), open land (77.4%), and shrubland (45.2%), while primary and secondary forests areas declined by 21.1% and 23.1%, respectively. These changes caused the Curve Number value to increase from 69.5 in 1990 to 71.9 in 2024. The spatial distribution analysis shows increases in areas with medium (28%) and high (6.5%) CN values. In line with the 46.6% increase in rainfall, the surface runoff volume increase from 1,704,979,578 m³ to 2,572,791,394 m³, or by 46.7%. In parallel, the runoff coefficient (C) increased from 0.928 to 0.955, indicating decreased infiltration capacity due to land use changes. These findings suggest that land-use changes directly increase CN and C values, contributing to higher surface runoff and flood risk in the Keureuto Watershed.